Preparation method of modified waterborne polyurethane antibacterial film, synthetic leather and application in automotive interior
Patent Information
- Application Number
- CN202610763693.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-20
AI Technical Summary
[0002]聚氨酯材料因其优异的力学性能、耐化学性和加工适应性,已广泛应用于汽车内饰领域,包括座椅面料、门板包覆、仪表台表皮等关键部件,但传统溶剂型聚氨酯体系存在有机溶剂残留高、VOC排放超标、环境友好性差等问题,无法满足现代汽车工业对环保材料的严格要求,同时水性聚氨酯在汽车复杂使用环境下的力学稳定性、耐候性和功能持久性仍面临重大挑战
[0024](1)本申请提供了一种改性水性聚氨酯抗菌薄膜的制备方法,通过高低HLB值双表面活性剂在疏水与亲水微区界面形成复合界面膜,在溶剂挥发过程中作为软模板诱导体系发生规则微相分离以形成微孔雏形,而在体系达到特定溶剂残留量引发流变学粘弹态转变时同步实施降温与垂直拉伸,利用机械外场克服微相分离产生的界面能势垒,促使软模板诱导的无序微孔沿垂直受力方向发生塑性形变与贯通,打破了传统体系无法原位构建取向微结构的壁垒,在纯薄膜内部原位生成垂直贯通的定向导湿微管网络,进而赋予经二次复合制得的合成革持续稳定的单向导湿能力与长效抗菌性能。
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane material preparation technology, and more particularly to a method for preparing a modified waterborne polyurethane antibacterial film and its application in synthetic leather and automotive interiors. Background Technology
[0002] Polyurethane materials have been widely used in the automotive interior field due to their excellent mechanical properties, chemical resistance and processing adaptability, including key components such as seat fabrics, door panel coverings and dashboard skins. However, traditional solvent-based polyurethane systems have problems such as high organic solvent residue, excessive VOC emissions and poor environmental friendliness, which cannot meet the strict requirements of the modern automotive industry for environmentally friendly materials. At the same time, waterborne polyurethane still faces significant challenges in terms of mechanical stability, weather resistance and functional durability under the complex use environment of automobiles.
[0003] Automotive interior materials are in a closed, warm, and humid environment for a long time, and are frequently in contact with the human body, making them extremely prone to the growth of bacteria, mold, and other microorganisms. This can lead to odors, material degradation, and health risks. Existing polyurethane synthetic leather has a large number of microorganisms on its surface. Traditionally added antibacterial agents through physical blending are unevenly dispersed in the polyurethane matrix and are prone to migration and precipitation, resulting in a decrease in antibacterial effect and an inability to achieve long-term antibacterial protection. This seriously restricts the hygienic and safe performance of automotive interior materials.
[0004] During the preparation of waterborne polyurethane films, improper control of solvent evaporation rate leads to the formation of irregular pore structures with wide pore size distribution and poor connectivity. These micropores become channels for water penetration and microbial growth. At the same time, during the gradient drying process, rapid skin formation on the surface hinders the diffusion of internal solvents, forming a closed-pore structure. This results in stress concentration inside the film, a decrease in mechanical properties, and uneven porosity, which directly affects the film's moisture permeability, air permeability, and surface smoothness, failing to meet the dual requirements of automotive interior materials for both appearance and function.
[0005] The irregular pore structure inside the polyurethane film interacts with the antibacterial agent, resulting in a synergistic degradation effect. The pore network accelerates the migration and loss of the antibacterial agent, while the high humidity environment inside the pores promotes the oxidative decomposition of the antibacterial agent, leading to a sharp decline in antibacterial efficiency under humid and hot conditions. On the other hand, the uneven deposition of antibacterial agent particles on the pore walls disrupts the continuity of the polyurethane molecular chains, reducing the tensile strength and elongation at break of the film. This performance degradation is further aggravated under the wide temperature range of use in automotive interiors, making it impossible for the material to simultaneously maintain both antibacterial function and mechanical stability. Summary of the Invention
[0006] This invention overcomes the shortcomings of the prior art and provides a method for preparing a modified waterborne polyurethane antibacterial film, as well as its application in synthetic leather and automotive interiors.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing a modified waterborne polyurethane antibacterial film, comprising the following steps:
[0008] S1. Dissolve polyurethane resin in an organic solvent to obtain a polyurethane base solution, and add thermoplastic elastomer and nano titanium dioxide antibacterial agent to the polyurethane base solution to obtain a blend matrix solution;
[0009] S2. Add a mixture of a first surfactant and a second surfactant to the blended matrix solution and emulsify and disperse to obtain a film-forming precursor solution; the HLB value of the first surfactant is 4.3-4.7, the HLB value of the second surfactant is 15.0-16.7, and the mass ratio of the first surfactant to the second surfactant is 3:1-5:1.
[0010] S3. The film-forming precursor solution is coated onto a release carrier, and the first stage of solvent evaporation is carried out;
[0011] S4. The semi-dry membrane treated in step S3 is subjected to a second stage of solvent evaporation;
[0012] S5. Cool and shape the semi-dry film processed in step S4;
[0013] S6. Peel the film treated in step S5 from the release carrier to obtain a modified waterborne polyurethane antibacterial film.
[0014] In a preferred embodiment of the present invention, in step S1, the polyurethane resin is stirred and dissolved at 40-50°C for 2-3 hours, the solid content of the polyurethane base solution is 18-22 wt%, the mass of the thermoplastic elastomer accounts for 8-12 wt% of the mass of the polyurethane resin, the mass of the nano titanium dioxide antibacterial agent accounts for 1-3 wt% of the mass of the polyurethane resin, and the mixture is stirred at 50-60°C for 1-2 hours.
[0015] In a preferred embodiment of the present invention, in step S1, the organic solvent is selected from at least one of N,N-dimethylformamide, tetrahydrofuran, and butanone; the thermoplastic elastomer is selected from styrene-ethylene-butene-styrene block copolymer or methyl methacrylate-butadiene-styrene copolymer, and its weight-average molecular weight is 8 × 10⁻⁶. 4 -1.5×10 5 .
[0016] In a preferred embodiment of the present invention, in step S2, the first surfactant is Span-80 or Span-60; the second surfactant is Tween-20 or Tween-80; the total amount of the two surfactants added accounts for 0.8-1.5 wt% of the mass of the polyurethane resin; the rotation speed of emulsification dispersion is 800-1200 r / min, and the time is 25-35 min.
[0017] In a preferred embodiment of the present invention, in step S3, the thickness of the wet film after coating is 150-250 μm, the temperature of solvent evaporation in the first stage is 65-75℃, the relative humidity is 30-40%, the evaporation time is 8-12 min, and the residual amount of organic solvent in the system after evaporation is 20-25 wt%.
[0018] In a preferred embodiment of the present invention, in step S4, the temperature of solvent evaporation in the second stage is 85-95°C, the evaporation time is 6-10 min, and the residual amount of organic solvent in the system after evaporation is 12-15 wt%.
[0019] In a preferred embodiment of the present invention, in step S5, the cooling and setting temperature is 5-10°C, a tensile force perpendicular to the film surface is applied, the tensile ratio is 1.3-1.8 times, and the cooling and setting time is 3-5 min; subsequently, heat treatment is carried out at 110-130°C for 8-12 min.
[0020] In a preferred embodiment of the present invention, in step S6, the peeled film is conditioned for 24-48 hours in an environment of 23-25°C and 50-55% relative humidity.
[0021] To achieve the above objectives, the second technical solution adopted by the present invention is as follows: a modified waterborne polyurethane antibacterial synthetic leather, comprising a modified waterborne polyurethane antibacterial film and a base fabric layer; the modified waterborne polyurethane antibacterial film is laminated with the base fabric layer by hot pressing or roller coating with adhesive.
[0022] To achieve the above objectives, the third technical solution adopted by the present invention is: the application of modified waterborne polyurethane antibacterial synthetic leather in automotive interiors, wherein the synthetic leather is used as a surface covering material for automotive seats, automotive door panels or automotive dashboards.
[0023] This invention addresses the shortcomings of the prior art and has the following beneficial effects:
[0024] (1) This application provides a method for preparing a modified waterborne polyurethane antibacterial film. A composite interface film is formed at the interface of hydrophobic and hydrophilic micro-regions by two surfactants with high and low HLB values. During the solvent evaporation process, the film acts as a soft template to induce regular microphase separation in the system to form micropore prototypes. When the system reaches a specific amount of residual solvent to induce a rheological viscoelastic state transition, cooling and vertical stretching are carried out simultaneously. The mechanical external field is used to overcome the interfacial energy barrier generated by microphase separation, which causes the disordered micropores induced by the soft template to undergo plastic deformation and interconnection along the vertical force direction. This breaks the barrier that the traditional system cannot construct oriented microstructures in situ. A vertically interconnected directional moisture-wicking microtube network is generated in situ inside the pure film, thereby endowing the synthetic leather prepared by secondary composite with continuous and stable unidirectional moisture-wicking ability and long-lasting antibacterial properties.
[0025] (2) In this invention, the low HLB surfactant is tightly adsorbed onto the hydrophobic micro-region interface of the antibacterial agent and the thermoplastic elastomer through its hydrophobic tail chain, reducing the interfacial free energy and forming an initial coating layer to inhibit the macroscopic migration and aggregation of the dispersed phase. Meanwhile, the high HLB surfactant extends outward into the polyurethane continuous phase with its hydrophilic head group, and is arranged in a molecular-level staggered manner with the low HLB component at the phase interface. Through the steric hindrance effect, the compactness and thermodynamic disturbance resistance of the initial coating layer are greatly enhanced, and a high-strength composite interfacial film is constructed between the dispersed phase and the continuous phase. This ensures that the antibacterial component maintains a highly uniform macroscopic distribution state throughout the solvent evaporation process, thereby eliminating the local stress concentration defects caused by the aggregation and precipitation of the antibacterial agent from the root, and ensuring the integrity of the continuous mechanical network of the film and the long-term stability of the antibacterial function.
[0026] (3) In this invention, when the organic solvent in the system evaporates to a specific residual range, the polymer matrix undergoes a viscoelastic rheological transformation. The chain segments exhibit reversible motion activity in a highly elastic state and the network has an elastic modulus that resists macroscopic fracture. This provides a physical substrate for the pores formed by microphase separation that can undergo elastic response. Under this state, the cooling and vertical stretching coupling processes are implemented simultaneously. The cooling operation instantly increases the apparent viscosity of the system, locking the chain segment motion capability in the optimal highly elastic deformation range. The vertical stretching external field inputs directional mechanical work to the highly elastic network to overcome the micropore interface energy barrier, forcing the disordered micropores to undergo plastic yielding and extension. The thermodynamically driven disordered phase separation structure is precisely transformed into a mechanically induced anisotropic microtube network. While constructing a high-strength vertical load-bearing skeleton inside to resist external mechanical damage, a through-type directional moisture-guiding channel is generated, achieving a high degree of unity between mechanical stability and microstructure functionality. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 This is a flowchart illustrating the method steps of a preferred embodiment of the present invention. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0031] Application Overview:
[0032] When antibacterial agents are introduced into traditional polyurethane films, the antibacterial components are difficult to disperse evenly in the polyurethane matrix and are prone to migration and precipitation. At the same time, the addition of antibacterial agents will interfere with the arrangement of polyurethane molecular chains, destroying the continuity and density of the material. The pore structure naturally formed by polyurethane during film formation provides channels for the loss of antibacterial agents. This dual effect of uneven antibacterial agent dispersion and matrix structure destruction makes it difficult for the material to maintain long-term antibacterial efficacy and ensure basic mechanical strength.
[0033] This application employs a precise combination of surfactants with high and low hydrophilic-lipophilic balance values. The low-value surfactant can deeply bind to the hydrophobic regions of polyurethane, while the high-value surfactant effectively stabilizes the hydrophilic interface. The two work together to form a stable emulsion system. In addition, the solvent evaporation is controlled in stages, and a combined treatment of low-temperature cooling and vertical stretching is implemented when the material is in a specific viscoelastic state. This allows the antibacterial components to be firmly locked in the matrix network during the directional alignment of the polyurethane molecular chains, while optimizing the internal pore structure of the material.
[0034] This technical solution enables the antibacterial components to be uniformly distributed and stably retained in the polyurethane matrix. The directional arrangement of polyurethane molecular chains significantly enhances the internal bonding strength of the material. The antibacterial function and mechanical properties are coordinated and unified at the microstructural level, ultimately resulting in a polyurethane film product that has both long-lasting antibacterial ability and maintains excellent physical strength.
[0035] Waterborne polyurethane resin (WPU-3000, 40% solids content, Covestro Polymers (China) Co., Ltd.); Styrene-ethylene-butene-styrene block copolymer (SEBS YH-503, Baling Petrochemical Co., Ltd.); Span-80 (sorbitan monooleate, HLB value 4.3, Sinopharm Chemical Reagent Co., Ltd.); Tween-80 (polyoxyethylene sorbitan monooleate, HLB value 15.7, Sinopharm Chemical Reagent Co., Ltd.); XH-3000 (cocamidopropyl hydroxysulfonate betaine, HLB value (pH 7.0) 13.2, Guangzhou Xinghong Chemical Co., Ltd.); N,N-dimethylformamide (DMF, analytical grade, Sinopharm Chemical Reagent Co., Ltd.); Nonwoven fabric base (180 g / m², Jiangsu Shenghong Group Co., Ltd.); Nano titanium dioxide antibacterial agent (model VK-T25H, anatase type, average particle size 20 nm, Nanjing Xianfeng Nanomaterials Technology Co., Ltd.).
[0036] like Figure 1 As shown, a method for preparing a modified waterborne polyurethane antibacterial film includes the following steps:
[0037] S1. Dissolve polyurethane resin in an organic solvent to obtain a polyurethane base solution. Add thermoplastic elastomer and nano-titanium dioxide antibacterial agent to the polyurethane base solution to obtain a blend matrix solution.
[0038] S2. Add a mixture of the first surfactant and the second surfactant to the blend matrix solution and emulsify and disperse to obtain a film-forming precursor solution; the HLB value of the first surfactant is 4.3-4.7, the HLB value of the second surfactant is 15.0-16.7, and the mass ratio of the first surfactant to the second surfactant is 3:1-5:1.
[0039] S3. Coat the film-forming precursor solution onto the release carrier and perform the first stage of solvent evaporation;
[0040] S4. The semi-dry membrane treated in step S3 is subjected to a second stage of solvent evaporation;
[0041] S5. Cool and shape the semi-dry film processed in step S4;
[0042] S6. Peel the film treated in step S5 from the release carrier to obtain a modified waterborne polyurethane antibacterial film.
[0043] The following section elaborates on each step of the preparation method.
[0044] In step S1:
[0045] Polyurethane resin is dissolved in an organic solvent to obtain a polyurethane base solution. A thermoplastic elastomer is then added to the polyurethane base solution to obtain a blend matrix solution.
[0046] More specifically, in step S1, the polyurethane resin is stirred and dissolved at 40-50℃ for 2-3 hours, the solid content of the polyurethane base solution is 18-22wt%, the mass of the thermoplastic elastomer accounts for 8-12wt% of the mass of the polyurethane resin, the mass of the nano titanium dioxide antibacterial agent accounts for 1-3wt% of the mass of the polyurethane resin, and the solution is stirred at 50-60℃ for 1-2 hours.
[0047] Furthermore, the organic solvent is selected from at least one of N,N-dimethylformamide, tetrahydrofuran, and butanone; the thermoplastic elastomer is selected from styrene-ethylene-butene-styrene block copolymer or methyl methacrylate-butadiene-styrene copolymer, with a weight-average molecular weight of 8 × 10⁻⁶. 4 -1.5×10 5 .
[0048] In this article, polyurethane base solution refers to the macroscopically homogeneous liquid system formed after polyurethane resin is completely dissolved in an organic solvent. Blended matrix solution refers to a mixed liquid system in which a thermoplastic elastomer is introduced into the polyurethane base solution and dispersed at the molecular level.
[0049] It should be noted that dissolving polyurethane resin in an organic solvent is to allow the solvent molecules to break the hydrogen bonds and van der Waals forces between the polyurethane molecular chains, thus promoting the full extension of the polymer chains. Setting a specific solids content parameter is to give the solution an appropriate initial viscosity to match the leveling requirements of the subsequent coating process.
[0050] The 20wt% solid content refers to the percentage of polyurethane resin solids in the total solution mass. The total solution specifically includes the aqueous polyurethane dispersion, organic solvent, antibacterial agent, and elastomer. The specific feeding process is as follows: Weigh 100g of aqueous polyurethane resin with a solid content of 40%, which includes 40g of pure polyurethane resin solids and 60g of water. Add 100g of N,N-dimethylformamide (DMF) and stir at 50℃ for 2 hours. DMF is miscible with water and disrupts the colloidal double layer, allowing the polyurethane resin to be distributed in a molecularly dissolved state in the mixed solvent. At this point, the total mass of the system is 200g, and the pure resin solid content is 20wt%.
[0051] The principle of adding thermoplastic elastomers to the system is to utilize the microphase separation characteristics of hard and soft segments in thermoplastic elastomers to build a physical cross-linking network inside the polyurethane matrix. This physical cross-linking network can absorb and dissipate externally applied mechanical stress in subsequent processes, preventing the film from brittle fracture under stress, thereby ensuring the integrity of the internal microtubule structure.
[0052] In step S2:
[0053] A mixture of a first surfactant and a second surfactant is added to a blend matrix solution and emulsified and dispersed to obtain a film-forming precursor solution; the HLB value of the first surfactant is 4.3-4.7, the HLB value of the second surfactant is 15.0-16.7, and the mass ratio of the first surfactant to the second surfactant is 3:1-5:1.
[0054] More specifically, in step S2, the first surfactant is Span-80 or Span-60; the second surfactant is Tween-20 or Tween-80; the total amount of the two surfactants added accounts for 0.8-1.5 wt% of the mass of the polyurethane resin; the rotation speed of emulsification dispersion is 800-1200 r / min, and the time is 25-35 min.
[0055] In this article, the film-forming precursor liquid refers to a homogeneous liquid mixture that has completed microscopic phase regulation and has the potential to spontaneously form a specific pore structure during solvent evaporation.
[0056] Understandably, the first surfactant has a low HLB value, exhibiting strong oleophilicity, and tends to adsorb at the interface between hydrophobic microdomains such as thermoplastic elastomers and organic solvents; the second surfactant has a high HLB value, exhibiting strong hydrophilicity, and tends to distribute in the highly polar polyurethane segment-rich regions. The purpose of emulsification and dispersion is to allow these two surfactants to interlock within the solution under the action of a shear field, forming a tight composite interfacial film. Setting a specific mass ratio parameter ensures the hydrophilic-hydrophobic balance of the composite interfacial film, enabling it to act as a stable soft template during the subsequent solvent evaporation stage, guiding the polymer matrix to undergo regularly arranged microphase separation, thereby determining the initial morphology and distribution density of the microtube network.
[0057] In step S3:
[0058] The film-forming precursor solution was coated onto the release carrier for the first stage of solvent evaporation.
[0059] More specifically, in step S3, the thickness of the wet film after coating is 150-250 μm, the temperature of solvent evaporation in the first stage is 65-75℃, the relative humidity is 30-40%, the evaporation time is 8-12 min, and the residual amount of organic solvent in the system after evaporation is 20-25 wt%.
[0060] Furthermore, the release carrier is a PET film or release paper with a surface treated with silicone or fluoropolymer resin, and the surface peel force between it and the film-forming pretreatment liquid is at an extremely low level.
[0061] It is important to emphasize that coating the pre-film-forming solution onto the release carrier, rather than directly onto the base fabric, is to completely eliminate the abnormal suction interference of the internal fiber capillaries on the solvent evaporation process, ensuring the consistency of solvent evaporation rates on the upper and lower surfaces of the film. This provides an undisturbed molding environment for the vertical interconnection of the microtube network. The purpose of the first-stage solvent evaporation is to thermodynamically drive the escape of a small amount of low-boiling-point solvent from the system surface, initially increasing the polymer concentration and establishing a concentration gradient from the surface to the interior of the system. This provides the necessary thermodynamic supersaturation driving force for the next stage of deep phase separation.
[0062] In step S4:
[0063] The semi-dry membrane treated in step S3 is subjected to a second stage of solvent evaporation.
[0064] More specifically, in step S4, the temperature of solvent evaporation in the second stage is 85-95℃, the evaporation time is 6-10 min, and the residual amount of organic solvent in the system after evaporation is 12-15 wt%.
[0065] In this article, semi-dry film refers to a gel-like film that loses macroscopic fluidity but still has the ability to move microscopic chain segments after some solvent has evaporated.
[0066] The principle is that as the temperature rises, the organic solvent evaporates rapidly, and the polymer concentration in the system increases sharply. When the residual organic solvent in the system reaches 12-15 wt%, the system undergoes a rheological phase transition, that is, a transition between storage modulus and loss modulus. Under this specific rheological state, the polymer matrix changes from a viscous flow state to a highly elastic state, the chain segments have sufficient kinematic activity, and the overall network of the system has an elastic modulus to resist macroscopic damage, thus giving the semi-dry film the physical basis to withstand the action of external mechanical forces.
[0067] In step S5:
[0068] The semi-dry film processed in step S4 is then cooled and shaped.
[0069] More specifically, in step S5, the cooling and setting temperature is 5-10℃, a tensile force perpendicular to the film surface is applied, the stretching ratio is 1.3-1.8 times, and the cooling and setting time is 3-5 min; then, heat treatment is carried out at 110-130℃ for 8-12 min.
[0070] Furthermore, the application of a tensile force perpendicular to the film surface is achieved by a stretching device with multiple sets of clamping rollers.
[0071] It should be noted that the key improvement of this invention lies in the simultaneous coupling of cooling and stretching. Rapidly lowering the temperature to 5-10°C when the system is within the viscoelastic window is to significantly increase the apparent viscosity of the system through a thermodynamic freezing effect, instantly freezing the chain segment mobility in a state capable of elastic deformation. Applying a stretching force perpendicular to the film surface aims to overcome the surface energy barrier generated by microphase separation using a mechanical external field, causing the previously formed disordered microporous structure induced by the soft template to undergo plastic deformation, stretching, and interconnection along the vertical direction, thereby transforming it into a directional moisture-guiding microtube network. High-temperature heat treatment after stretching is performed to induce microcrystalline rearrangement of the hard segment phase of the thermoplastic elastomer, while simultaneously evaporating residual solvents, eliminating internal stress generated by stretching within the film, and achieving permanent physical locking of the directional microtube structure.
[0072] In step S6:
[0073] The film treated in step S5 is peeled off from the release carrier to obtain a modified waterborne polyurethane antibacterial film.
[0074] More specifically, in step S6, the peeled film is conditioned for 24-48 hours in an environment of 23-25°C and 50-55% relative humidity.
[0075] Understandably, the conditioning operation refers to placing the dry film in a constant temperature and humidity environment to allow the stress distribution of the microtube structure inside the film to tend to be balanced, while avoiding sudden changes in environmental humidity that could cause the microtube pore walls to absorb moisture and swell or undergo secondary shrinkage, thus ensuring the final dimensional stability of the film and the integrity of its microstructure.
[0076] Based on the preparation method of any of the above embodiments, the present invention also provides a modified waterborne polyurethane antibacterial synthetic leather. In one embodiment, the synthetic leather includes a prepared modified waterborne polyurethane antibacterial film and a base fabric layer. The modified waterborne polyurethane antibacterial film is laminated to the base fabric layer by hot pressing or roller coating with adhesive.
[0077] More specifically, when using hot-press lamination, the hot-pressing temperature is 120-140℃, the pressure is 0.5-2.0MPa, and the time is 30-60s. When using roller coating with adhesive, the adhesive is a polyurethane-based water-based adhesive, and the coating amount is 80-120g / m².2 .
[0078] The principle is that by first preparing a pure film without a base fabric and then performing a secondary composite, the physical obstruction of the microtube network evolution process by the base fabric during the film-forming stage can be avoided. During the hot-pressing composite stage, the microtube network on the surface of the pure film can be partially embedded into the pores of the base fabric layer under the action of pressure and temperature, forming a mechanically interlocking structure. This ensures that the synthetic leather has excellent unidirectional moisture-wicking and antibacterial properties while meeting the peel strength requirements of automotive interior materials.
[0079] Based on the above-mentioned modified waterborne polyurethane antibacterial synthetic leather, the present invention also provides an application of modified waterborne polyurethane antibacterial synthetic leather in automotive interiors. In one embodiment, the synthetic leather is used as a surface covering material for automotive seats, automotive door panels, or automotive dashboards.
[0080] It should be noted that the interior of a car is a closed, high-temperature, and high-humidity microenvironment with strong sunlight, making it easy for sweat from occupants to accumulate on the seat surface. When this synthetic leather is used as a surface covering material, its internal directional moisture-guiding microvascular network can utilize capillary pressure difference to quickly pump liquid sweat from the contact side to the non-contact side for evaporation and dissipation. At the same time, it blocks the reverse penetration of external moisture. Combined with long-lasting antibacterial properties, it effectively inhibits the growth of microorganisms and the generation of odors on the interior surface.
[0081] Example 1:
[0082] This embodiment describes a method for preparing a modified waterborne polyurethane antibacterial film, comprising the following steps:
[0083] S1 dissolves polyurethane resin in an organic solvent to obtain a polyurethane base solution. A thermoplastic elastomer and a nano-titanium dioxide antibacterial agent are then added to the polyurethane base solution to obtain a blend matrix solution. The polyurethane resin is stirred and dissolved at 50°C for 2 hours. The solid content of the polyurethane base solution is 20 wt%, the mass of the thermoplastic elastomer accounts for 12 wt% of the mass of the polyurethane resin, and the mass of the nano-titanium dioxide antibacterial agent accounts for 2 wt% of the mass of the polyurethane resin. The solution is then stirred at 55°C for 1.5 hours.
[0084] The organic solvent is N,N-dimethylformamide; the thermoplastic elastomer is a styrene-ethylene-butene-styrene block copolymer with a weight-average molecular weight of 1.2 × 10⁻⁶. 5 .
[0085] S2. A mixture of a first surfactant and a second surfactant is added to the blend matrix solution and emulsified and dispersed to obtain a film-forming precursor solution; the HLB value of the first surfactant is 4.3, the HLB value of the second surfactant is 15.7, and the mass ratio of the first surfactant to the second surfactant is 3:1.
[0086] The first surfactant is Span-80; the second surfactant is Tween-80; the total amount of the two surfactants added accounts for 1.2 wt% of the mass of the polyurethane resin; the emulsification and dispersion speed is 800 r / min and the time is 30 min.
[0087] S3. The film-forming precursor solution was coated onto the release carrier, and the first stage of solvent evaporation was carried out. The thickness of the wet film after coating was 200 μm, the temperature of the first stage of solvent evaporation was 70℃, the relative humidity was 36%, the evaporation time was 10 min, and the residual amount of organic solvent in the system after evaporation was 20 wt%.
[0088] S4. The semi-dry membrane treated in step S3 is subjected to a second stage of solvent evaporation; the temperature of the second stage solvent evaporation is 90°C, and the evaporation time is controlled until the residual amount of organic solvent in the system after evaporation is 12wt%.
[0089] S5. The semi-dry film treated in step S4 is subjected to cooling and shaping treatment; the cooling and shaping temperature is 8°C, a tensile force perpendicular to the film surface is applied, the stretching ratio is 1.6 times, and the cooling and shaping time is 4 min; then it is heat-treated at 120°C for 10 min.
[0090] S6. The film treated in step S5 is peeled off from the release carrier to obtain a modified waterborne polyurethane antibacterial film. The peeled film is conditioned for 48 hours at 24°C and 55% relative humidity.
[0091] Example 2:
[0092] The difference between this embodiment and Embodiment 1 is that the mass ratio of the first surfactant to the second surfactant is 4:1, while the rest are the same.
[0093] Example 3:
[0094] The difference between this embodiment and Embodiment 1 is that the mass ratio of the first surfactant to the second surfactant is 5:1, while the rest are the same.
[0095] Example 4:
[0096] The difference between this embodiment and embodiment 2 is that the residual amount of organic solvent in the system after evaporation in S3 is 22.5 wt%, while the rest are the same.
[0097] Example 5:
[0098] The difference between this embodiment and embodiment 2 is that the residual amount of organic solvent in the system after evaporation in S3 is 25 wt%, while the rest are the same.
[0099] Comparative Example 1:
[0100] The difference between this comparative example and Example 1 is that the mass ratio of the first surfactant to the second surfactant is 2:1, while the rest are the same.
[0101] Comparative Example 2:
[0102] The difference between this comparative example and Example 1 is that the mass ratio of the first surfactant to the second surfactant is 4:1, while the rest are the same.
[0103] Comparative Example 3:
[0104] The difference between this comparative example and Example 2 is that the residual amount of organic solvent in the system after evaporation in S3 is 17.5 wt%, while the rest are the same.
[0105] Comparative Example 4:
[0106] The difference between this comparative example and Example 2 is that the residual amount of organic solvent in the system after evaporation in S3 is 27.5 wt%, while the rest are the same.
[0107] Comparative Example 5:
[0108] This comparative example describes a method for preparing a modified waterborne polyurethane antibacterial film, comprising the following steps:
[0109] S1. Dissolve polyurethane resin in an organic solvent to obtain a polyurethane base solution. Add thermoplastic elastomer and nano-titanium dioxide antibacterial agent to the polyurethane base solution to obtain a blend matrix solution. Stir and dissolve the polyurethane resin at 50°C for 2 hours. The solid content of the polyurethane base solution is 20 wt%, the mass of thermoplastic elastomer accounts for 12 wt% of the mass of polyurethane resin, and the mass of nano-titanium dioxide antibacterial agent accounts for 2 wt% of the mass of polyurethane resin. Stir at 55°C for 1.5 hours.
[0110] The organic solvent is N,N-dimethylformamide; the thermoplastic elastomer is a styrene-ethylene-butene-styrene block copolymer with a weight-average molecular weight of 1.2 × 10⁻⁶. 5 .
[0111] S2. Add an amphoteric surfactant to the blend matrix solution and emulsify and disperse to obtain a film-forming precursor solution; the amphoteric surfactant is cocamidopropyl hydroxysulfonate betaine;
[0112] The amount of amphoteric surfactant added accounts for 1.2 wt% of the mass of polyurethane resin; the emulsification and dispersion speed is 800 r / min and the time is 30 min.
[0113] S3. The film-forming precursor solution is coated onto the release carrier, and the first stage of solvent evaporation is carried out. The thickness of the wet film after coating is 200 μm, the temperature of the first stage of solvent evaporation is 70℃, the relative humidity is 36%, and the evaporation time is controlled until the residual amount of organic solvent in the system after evaporation is 20 wt%.
[0114] S4. The semi-dry membrane treated in step S3 is subjected to a second stage of solvent evaporation; the temperature of the second stage solvent evaporation is 90°C, and the evaporation time is controlled until the residual amount of organic solvent in the system after evaporation is 12wt%.
[0115] S5. The semi-dry film treated in step S4 is subjected to cooling and shaping treatment; the cooling and shaping temperature is 8°C, a tensile force perpendicular to the film surface is applied, the stretching ratio is 1.6 times, and the cooling and shaping time is 4 min; then it is heat-treated at 120°C for 10 min.
[0116] S6. The film treated in step S5 is peeled off from the release carrier to obtain a modified waterborne polyurethane antibacterial film. The peeled film is conditioned for 48 hours at 24°C and 55% relative humidity.
[0117] Comparative Example 6:
[0118] This comparative example describes a method for preparing a modified waterborne polyurethane antibacterial film, comprising the following steps:
[0119] S1. Dissolve polyurethane resin in an organic solvent to obtain a polyurethane base solution. Add thermoplastic elastomer and nano-titanium dioxide antibacterial agent to the polyurethane base solution to obtain a blend matrix solution. Stir and dissolve the polyurethane resin at 50°C for 2 hours. The solid content of the polyurethane base solution is 20 wt%, the mass of thermoplastic elastomer accounts for 12 wt% of the mass of polyurethane resin, and the mass of nano-titanium dioxide antibacterial agent accounts for 2 wt% of the mass of polyurethane resin. Stir at 55°C for 1.5 hours.
[0120] The organic solvent is N,N-dimethylformamide; the thermoplastic elastomer is a styrene-ethylene-butene-styrene block copolymer with a weight-average molecular weight of 1.2 × 10⁻⁶. 5 .
[0121] S2. A mixture of a first surfactant and a second surfactant is added to the blend matrix solution and emulsified and dispersed to obtain a film-forming precursor solution; the HLB value of the first surfactant is 4.3, the HLB value of the second surfactant is 15.7, and the mass ratio of the first surfactant to the second surfactant is 3:1.
[0122] The first surfactant is Span-80; the second surfactant is Tween-80; the total amount of the two surfactants added accounts for 1.2 wt% of the mass of the polyurethane resin; the emulsification and dispersion speed is 800 r / min and the time is 30 min.
[0123] S3. The film-forming precursor solution is coated onto the release carrier and the solvent is evaporated. The thickness of the wet film after coating is 200 μm, the solvent evaporation temperature is 80℃, the relative humidity is 36%, and the evaporation time is controlled until the residual amount of organic solvent in the system is 12 wt% after evaporation.
[0124] S4. The semi-dry film treated in step S4 is subjected to cooling and shaping treatment; the cooling and shaping temperature is 8°C, a tensile force perpendicular to the film surface is applied, the stretching ratio is 1.6 times, and the cooling and shaping time is 4 min; then it is heat-treated at 120°C for 10 min.
[0125] S5. The film treated in step S5 is peeled off from the release carrier to obtain a modified waterborne polyurethane antibacterial film. The peeled film is conditioned for 48 hours at 24°C and 55% relative humidity.
[0126] Test experiment:
[0127] Examples 1-5 and Comparative Examples 1-6 were subjected to emulsion average particle size testing, interfacial tension change rate testing, and birefringence value testing, respectively. The emulsion average particle size test involved testing the film-forming precursor liquid obtained in step S2 to directly obtain the average particle size of the antibacterial agent dispersed phase. The interfacial tension change rate test was conducted using a rotating drop interfacial tensiometer. The film-forming precursor liquid was placed in a test cell, and the change in interfacial tension over time was monitored under a constant temperature of 85°C. The rate of change in interfacial tension within the first ten minutes was calculated. The birefringence value test involved cutting the film sample into 10×10mm square pieces, placing them on a stage, adjusting the polarizer angle, and measuring the difference in refractive index parallel to and perpendicular to the stretching direction. Five different locations were tested for each sample, and the average value was taken. The test data are shown in Table 1.
[0128] Table 1 Test data of Examples 1-5 and Comparative Examples 1-6
[0129] Data source Average particle size of emulsion (μm) Interfacial tension change rate (%) Refractive index difference Example 1 0.22 4.4 0.012 Example 2 0.18 4.0 0.014 Example 3 0.20 4.3 0.013 Example 4 0.15 2.6 0.015 Example 5 0.17 4.1 0.014 Comparative Example 1 0.28 5.2 0.009 Comparative Example 2 0.29 5.4 0.008 Comparative Example 3 0.27 5.3 0.008 Comparative Example 4 0.28 5.4 0.006 Comparative Example 5 1.15 12.3 0.003 Comparative Example 6 0.30 4.9 0.001
[0130] As shown in Table 1, the refractive index difference of Examples 1-5 is greater than that of Comparative Examples 1-6, and the change rate of average particle size and interfacial tension of the emulsions in Examples 1-5 is less than that in Comparative Examples 1-6. Therefore, this application has advantages.
[0131] In Examples 1-3 and Comparative Examples 1-2, as the proportion of the first surfactant in the mass ratio of the first surfactant to the second surfactant gradually increases, the refractive index difference first increases and then decreases, while the changes in the average particle size and interfacial tension of the emulsion first decrease and then increase. This is because, with the initial increase in the proportion of the low-HLB value first surfactant, its strong hydrophobic properties synergistically construct a hydrophilic-hydrophobic balanced composite interfacial film with the high-HLB value second surfactant. This effectively enhances the anchoring and encapsulation ability of the hydrophobic microdomains of the antibacterial agent and thermoplastic elastomer, inhibits the macroscopic aggregation of dispersed phase droplets, and enables the precursor liquid system to obtain excellent dispersion stability and resistance to thermal disturbance. The ability to form a highly anisotropic microporous structure provides an ideal isotropic basis for uniform plastic deformation and highly oriented orientation during subsequent volatilization and stretching. However, when the proportion of the first surfactant increases excessively, the overall hydrophilic-hydrophobic balance of the system is disrupted, and the hydrophilicity of the composite interface film is significantly weakened, leading to desorption and recombination instability in the continuous phase. This causes the antibacterial agent dispersion phase to re-aggregate, and the system to undergo severe phase separation under thermodynamic conditions. This macroscopic disorder and surge in defects within the precursor liquid's internal structure result in localized stress concentration and irregular rupture of the system under subsequent vertical stretching, thus losing the ability to construct a highly anisotropic oriented microtube network. The preferred embodiment in Examples 1-3 is Example 2.
[0132] In Examples 2, 4-5, and Comparative Examples 3-4, as the residual amount of organic solvent in the system gradually increases after the volatilization in S3, the refractive index difference first increases and then decreases, while the changes in the average particle size and interfacial tension of the emulsion first decrease and then increase. This is because, with the initial increase in the residual amount of organic solvent in the system after the first stage of volatilization, a suitable solvation environment and chain segment mobility are retained within the system. This allows the dual-surfactant composite interfacial film to undergo sufficient interfacial rearrangement and structural self-optimization under a mild concentration gradient, effectively suppressing the macroscopic coarsening and demulsification tendency caused by premature desolvation of the dispersed phase. This provides a uniform microphase separation matrix for the subsequent second stage of volatilization to precisely enter the viscoelastic window and implement vertical stretching and shaping. The ideal precursor state of the microporous structure promotes highly directional deformation under the influence of an external field. However, when the residual organic solvent in the system increases excessively, the concentration gradient established in the early stage is too small, causing the system to face extreme solvent removal kinetic shocks when entering the second stage of high-temperature volatilization. The instantaneous huge thermodynamic supersaturation directly destroys the dynamic equilibrium of the composite interface film, triggering violent aggregation of the dispersed phase and macroscopic phase separation instability. At the same time, the excessive residual solvent has a deep plasticizing effect on the polymer network, causing the system to fall into a viscous flow state rather than a highly elastic deformation state when a vertical tensile external field is applied. It cannot effectively convert mechanical work into the directional orientation of the microtubule structure, ultimately causing the internal structural evolution to completely deviate from the construction path of the directional hygroscopic framework. The best embodiment is Example 4.
[0133] Comparative Example 5 uses a single amphoteric surfactant to replace the high and low HLB value compound system. This results in the loss of the strong anchoring effect of the low HLB value component at the hydrophobic micro-region interface and the synergistic effect of the steric hindrance provided by the high HLB value component. Consequently, it is impossible to construct a dense and thermodynamically stable composite interfacial film on the surface of the dispersed phase. This deterioration in the interfacial barrier strength makes it easy for hydrophobic components such as antibacterial agents to break through the interfacial constraints and undergo macroscopic aggregation under thermodynamic disturbances. This leads to a significant increase in the average particle size of the emulsion and violent fluctuations in interfacial tension. When the precursor system with this macroscopic aggregation defect enters the subsequent vertical stretching process, the non-uniform internal phase state will induce severe local stress concentration, causing the matrix to undergo disordered fracture rather than ordered plastic deformation under the stretching field. This completely loses the ability to construct a highly oriented anisotropic microtube network.
[0134] Comparative Example 6 retained the excellent high and low HLB value compound system, thus maintaining a highly uniform dispersion and excellent interfacial thermal stability in the pre-film formation liquid stage, exhibiting the same low emulsion average particle size and low interfacial tension change rate as Example 4; however, due to the complete removal of the cooling and vertical stretching coupling process within a specific solvent residue range, the system relies solely on the natural evaporation of the solvent to complete the structural evolution after crossing the viscoelastic window, resulting in the pore structure generated by the internal microphase separation being completely subject to disordered thermodynamic diffusion, lacking a mechanical external field to overcome the interfacial energy barrier to induce plastic deformation and interconnection of micropores in the vertical direction, ultimately forming only an isotropic random pore network inside the film, unable to generate any macroscopic optical anisotropic response.
[0135] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A method for preparing a modified waterborne polyurethane antibacterial film, characterized in that, Includes the following steps: S1. Dissolve polyurethane resin in an organic solvent to obtain a polyurethane base solution, and add thermoplastic elastomer and nano titanium dioxide antibacterial agent to the polyurethane base solution to obtain a blend matrix solution; S2. Add a mixture of a first surfactant and a second surfactant to the blended matrix solution and emulsify and disperse to obtain a film-forming precursor solution; the HLB value of the first surfactant is 4.3-4.7, the HLB value of the second surfactant is 15.0-16.7, and the mass ratio of the first surfactant to the second surfactant is 3:1-5:
1. S3. The film-forming precursor solution is coated onto a release carrier, and the first stage of solvent evaporation is carried out; S4. The semi-dry membrane treated in step S3 is subjected to a second stage of solvent evaporation; S5. Cool and shape the semi-dry film processed in step S4; S6. Peel the film treated in step S5 from the release carrier to obtain a modified waterborne polyurethane antibacterial film.
2. The method for preparing a modified waterborne polyurethane antibacterial film according to claim 1, characterized in that: In step S1, the polyurethane resin is stirred and dissolved at 40-50℃ for 2-3 hours, the solid content of the polyurethane base solution is 18-22wt%, the mass of the thermoplastic elastomer accounts for 8-12wt% of the mass of the polyurethane resin, the mass of the nano titanium dioxide antibacterial agent accounts for 1-3wt% of the mass of the polyurethane resin, and the mixture is stirred at 50-60℃ for 1-2 hours.
3. The method for preparing a modified waterborne polyurethane antibacterial film according to claim 1, characterized in that: In step S1, the organic solvent is selected from at least one of N,N-dimethylformamide, tetrahydrofuran, and methyl ethyl ketone; the thermoplastic elastomer is selected from styrene-ethylene-butene-styrene block copolymer or methyl methacrylate-butadiene-styrene copolymer, with a weight-average molecular weight of 8 × 10⁻⁶. 4 -1.5×10 5 .
4. The method for preparing a modified waterborne polyurethane antibacterial film according to claim 1, characterized in that: In step S2, the first surfactant is Span-80 or Span-60; the second surfactant is Tween-20 or Tween-80; the total amount of the two surfactants added accounts for 0.8-1.5 wt% of the mass of the polyurethane resin; the emulsification dispersion speed is 800-1200 r / min, and the time is 25-35 min.
5. The method for preparing a modified waterborne polyurethane antibacterial film according to claim 1, characterized in that: In step S3, the thickness of the wet film after coating is 150-250 μm, the temperature of solvent evaporation in the first stage is 65-75℃, the relative humidity is 30-40%, the evaporation time is 8-12 min, and the residual amount of organic solvent in the system after evaporation is 20-25 wt%.
6. The method for preparing a modified waterborne polyurethane antibacterial film according to claim 1, characterized in that: In step S4, the temperature for solvent evaporation in the second stage is 85-95℃, the evaporation time is 6-10 min, and the residual amount of organic solvent in the system after evaporation is 12-15 wt%.
7. The method for preparing a modified waterborne polyurethane antibacterial film according to claim 1, characterized in that: In step S5, the cooling and setting temperature is 5-10℃, a tensile force perpendicular to the film surface is applied, the stretching ratio is 1.3-1.8 times, and the cooling and setting time is 3-5 min; then, heat treatment is carried out at 110-130℃ for 8-12 min.
8. The method for preparing a modified waterborne polyurethane antibacterial film according to claim 1, characterized in that: In step S6, the peeled film is conditioned for 24-48 hours in an environment of 23-25°C and 50-55% relative humidity.
9. A modified waterborne polyurethane antibacterial synthetic leather, based on a method for preparing a modified waterborne polyurethane antibacterial film according to any one of claims 1-8, characterized in that, The invention includes a modified waterborne polyurethane antibacterial film and a base fabric layer; the modified waterborne polyurethane antibacterial film is laminated with the base fabric layer by hot pressing or roller coating with adhesive.
10. The application of a modified waterborne polyurethane antibacterial synthetic leather in automotive interiors, based on the modified waterborne polyurethane antibacterial synthetic leather according to claim 9, characterized in that... The synthetic leather is used as a surface covering material for car seats, car door panels, or car dashboards.